2020
DOI: 10.1111/apha.13513
|View full text |Cite
|
Sign up to set email alerts
|

An update on ACE2 amplification and its therapeutic potential

Abstract: The renin angiotensin system (RAS) plays an important role in the pathogenesis of variety of diseases. Targeting the formation and action of angiotensin II (Ang II), the main RAS peptide, has been the key therapeutic target for last three decades. ACE‐related carboxypeptidase (ACE2), a monocarboxypeptidase that had been discovered 20 years ago, is one of the catalytically most potent enzymes known to degrade Ang II to Ang‐(1‐7), a peptide that is increasingly accepted to have organ‐protective properties that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 126 publications
(344 reference statements)
0
35
0
2
Order By: Relevance
“… 29 , 30 Over the last decade, there has been an interest in ACE2 amplification for potential therapeutic use based primarily on preclinical studies. 31 ACE2 cleaves the phenylalanine amino acid from Ang II to form Ang 1–7 and from Ang I to form Ang 1–9. 21 The Ang1–7 peptide has vasoprotective effects mediated via activation of Mas—a G-protein–coupled receptor.…”
Section: Ace2 Is the Receptor For Sars-cov And Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations
“… 29 , 30 Over the last decade, there has been an interest in ACE2 amplification for potential therapeutic use based primarily on preclinical studies. 31 ACE2 cleaves the phenylalanine amino acid from Ang II to form Ang 1–7 and from Ang I to form Ang 1–9. 21 The Ang1–7 peptide has vasoprotective effects mediated via activation of Mas—a G-protein–coupled receptor.…”
Section: Ace2 Is the Receptor For Sars-cov And Sars-cov-2mentioning
confidence: 99%
“…In its full-length form, ACE2 has 805 amino acids, whereas in its soluble for,m ACE2 has only 740 amino acids. 31 Soluble ACE2 usually is barely detectable in the circulation or body fluids. It can be shed into the blood and tubular urine by ADAMS17 (ADAM metallopeptidase domain 17)—a disintegrin and metalloproteinase.…”
Section: Binding Of Sars-cov-2 To Ace2 Receptors and Internalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble ACE2 may act as a competitive interceptor of SARS-CoV-2 by preventing binding of the viral particle to surface-bound, full-length ACE2. Recently, nasal spray application [ 363 ] or systemic administration [ 330 ] of soluble ACE2 has been suggested for the treatment of COVID-19. Since plasma Ang-(1-7) levels were found to be reduced in a small cohort of COVID-19 patients [ 270 ], administration of soluble recombinant human ACE2 proteins may be beneficial as a novel biological therapeutic to limit or even combat the progression of an infection caused by coronaviruses that utilize ACE2 as a receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the antihypertensive effects of XNT and DIZE persist in ACE2 knockout mice and, notably, it has been reported that Ang-II degradation in vitro and ex vivo was unaffected by XNT and DIZE, suggesting that these compounds may have ACE2-independent actions [ 328 ]. However, it should also be noted that XNT and DIZE have been reported to cause a significant increase in ACE2 mRNA expression [ [329] , [330] , [331] ]. Currently, there is no clinically used ACE2-based therapeutic agent; however, preclinical studies and clinical trials are continuing [ 25 , 317 , 332 ].…”
Section: Pharmacology Of Ace2 and Ace2 Related Antiviral Treatmentsmentioning
confidence: 99%